Low-protein diets on broilers performance reared under different temperatures - Filho, Daniel Emygdio de Faria; Rosa, Paulo Sérgio; Figueiredo, Denise Fontana; Dahlke, Fabiano; Macari, Marcos; Furlan, Renato Luis (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate broilers performance, from 42 to 49 days, fed on low-protein diet and reared under different temperatures. Three hundred and sixty male broilers from Cobb-500 strain were randomly housed in a 3x3 factorial arrangement (environmental temperature of 20, 25 and 32oC and crude protein levels of 18.0, 16.5 and 15.0%) with four replicates of ten birds each. Performance and efficiency of nitrogen retention were impaired in broilers fed on low-protein diets and reared under temperature of 32ºC. Carcass, as well as thigh and drumstick increased in birds reared at hot temperature yield, however other parts yield, and abdominal fat deposition were not altered by the studied factors. Drumstick and thigh protein composition decreased in broilers reared under heat stress, while fat composition increased. Protein levels did not affect carcass composition. Low-protein diet impairs broiler performance in heat-exposed broilers from 42 to 49 days. However, broilers can be fed on low-protein diets under temperatures of 20 or 25ºC, because these temperatures did not affect broilers performance, carcass quality, and they promoted lower nitrogen excretion.